2022
DOI: 10.1002/ece3.9086
|View full text |Cite
|
Sign up to set email alerts
|

Predation on sentinel prey increases with increasing latitude in Brassica‐dominated agroecosystems

Abstract: In natural ecosystems, arthropod predation on herbivore prey is higher at lower latitudes, mirroring the latitudinal diversity gradient observed across many taxa. This pattern has not been systematically examined in human‐dominated ecosystems, where frequent disturbances can shift the identity and abundance of local predators, altering predation rates from those observed in natural ecosystems. We investigated how latitude, biogeographical, and local ecological factors influenced arthropod predation in Brassica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Arthropod predation of herbivore prey is often more prominent in natural environments at lower latitudes (Gray et al 2022), particularly in tropical regions. In an experiment in Subic Bay, Posa et al (2007) showed that arthropod predation was higher in closed canopies.…”
Section: Resultsmentioning
confidence: 99%
“…Arthropod predation of herbivore prey is often more prominent in natural environments at lower latitudes (Gray et al 2022), particularly in tropical regions. In an experiment in Subic Bay, Posa et al (2007) showed that arthropod predation was higher in closed canopies.…”
Section: Resultsmentioning
confidence: 99%
“…Biased detection should be especially problematic for prey that normally move, such as caterpillars and other larvae. Remarkably few studies have attempted to validate clay larvae against real larvae for comparing predation rates among sites (Greenop et al., 2019; Nagy et al., 2020), even though clay larvae are increasingly used for geographic comparisons (Gray et al., 2022; Roslin et al., 2017; Wallis et al., 2021; Zvereva et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Biased detection should be especially problematic for prey that normally move, such as caterpillars and other larvae. Remarkably few studies have attempted to validate clay larvae against real larvae for comparing predation rates among sites (Greenop et al, 2019; Nagy, Schellhorn, & Zalucki, 2020), even though clay larvae are increasingly used for geographic comparisons (Gray et al, 2022; Roslin et al, 2017; Wallis et al, 2021; Zvereva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%